Data Pesawat Udara Tanpa Awak Untuk Pendukung Analisis Dinamika Pesisir dan Erosi Pantai: Studi Kasus Pantai Pandansimo, Bantul, Daerah Istiwewa Yogyakarta - Fatchurohman, Hendy; Indrawati, Like; Ningtiyas, Iswanti Rahayu; Nadhira, Nur Anisa; Meliyasari, Sasvita Gevi (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
The coastal area is one of the most vulnerable areas to the threat of disaster due to the acceleration of climate change. One of the almost universal threats in coastal areas worldwide is coastal erosion. The coastal area of Bantul District, Special Region of Yogyakarta, is one of the areas that is quite severely affected by coastal erosion. This research aims to (1) determine the dynamics of the coastal area in the Pandansimo Beach area; (2) map the rate of abrasion at Pandansimo Beach, and (3) determine the leading causes of the coastal erosion that occurs. High-resolution Pleiades satellite data with a 50cm spatial resolution is used to determine the temporal changes in the coastline. In addition, satellite imagery from Google Earth is also used for the analysis from 2010-2021. The changes in the coastline are calculated using the DSAS software. Detailed morphological data was obtained from the acquisition of aerial photos using a multirotor unmanned aircraft. Based on the analysis, it was found that the process of coastal erosion dominated the dynamics of the coastal area. The average coastline regression value was recorded at 2.46 meters/year. Hydrodynamic and morphodynamic factors such as wind and wave forces, diminishing of fluvial sediment supply, and climate change are believed to cause coastal erosion.